Incidentally detected sellar spine in a patient with Cushing's syndrome: a case report. Issue 7 (July 2020) - Lee, Hyo-jae; Lee, Yun Young; Baek, Byung Hyun; Yoon, Woong; Kim, Seul Kee
Sellar spine, a bony spur extending anteriorly from the dorsum sellae, is a very rare anatomical variant. Several hypotheses regarding its etiology have been proposed, including the strongly supported theory of a cephalic ossified notochordal remnant. Sellar spine is usually detected incidentally in patients who have no definite symptoms, but several cases have reportedly accompanied endocrinopathies such as precocious puberty, hypopituitarism, or galactorrhea/oligomenorrhea. However, no published reports have described sellar spine in a patient with Cushing's syndrome. We herein report a case of sellar spine detected during the evaluation of Cushing's disease in a 29-year-old woman who underwent inferior petrosal sinus sampling, computed tomography, magnetic resonance imaging, and exploratory surgery. There was no evidence of a pituitary microadenoma, but a sellar spine was present in the operative field. Thus, the sellar spine might have caused Cushing's syndrome in this case, although the exact mechanism is unknown.